Indefiniteness between the eloquent and grammarians - Hamdan , Ibtisam; Zakaria , Shahada (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research discusses the concept of indefiniteness in grammarians, showing the attempts of grammarians to put an absolute to the indefiniteness, limit depending on agroup of linguistic and referential sings, and then to determine the degrees of indefiniteness, especially that some indefinite nouns are more indefinite than the others.